Assessment of Compliance of Glucosamine and Chondroitin Sulfate in Patients with Early Osteoarthritis of the Knee - Ajit Prakash Bhaskarwar; Ashish Pande; Kailash Pati Dev Jaidev (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Osteoarthritis (OA) is one of the common causes of knee disability. Depending on the stages of the disease, various treatment modalities are available. OA, being a degenerative and gradually progressive disease compliance with the treatment, has a major role in the outcome. Materials and Methods: The study was carried out at a tertiary care orthopedic center to assess the level of compliance of tablet glucosamine and chondroitin sulfate in patients with early OA of the knee. 100 consecutive patients visiting the outpatient department of orthopedics were included after clinical and radiological confirmation of diagnosis. Patients were given tablet glucosamine and chondroitin sulfate and followed up for 12 weeks. Compliance was assessed by the Morisky Medication Adherence Scale (MMAS). Results: One hundred patients consisting of 44 males and 56 females were enrolled. The average age of the study population was 51.06 ± 9.44 years. Response recorded by the MMAS showed good compliance in 46%, moderate in 36%, and poor in 18% of cases. A significant positive correlation was found with education, family support, and awareness of the disease, whereas a negative correlation was found with age, functional impairment, comorbidities, and polypharmacy. Conclusion: The study confirmed the existence of good compliance to glucosamine and chondroitin sulfate in patients with early OA of the knee. The variation in the reported level of compliance in the study population was due to factors such as literacy level, family status, functional status, associated medical illnesses, daily medicinal load, as well as awareness of the disease. Only a few studies have been conducted in developing countries on medication compliance, factors influencing it, and magnitude of the impact of noncompliance; hence, there is a need for more systematic studies.